How to Use Stories to Bring ‘Us’ and ‘Them’ Together - Neimand, Annie; Wright, Samantha (Stanford Social Innovation Review, 2019)
To build more inclusive movements, social advocacy organizations and activists need to create stories that can engage both familiar and new communities.